Pyrethrum marc supplement feeding to Dorper weaners at Katumani research station, Machakos - Allonby, E.; Kingoku, J.; Muhoya, K.; Muthoka, J.; Odhiambo, F.; Ogutu, E.; Preston, J.; Rakoazi, G. (1975)
Dorper weaners of about 9 months old at Katumani Research station in 1975 were divided in to 3 groups: Group I (20 males) 1 kg marc per day per head, Group II (20 males). 5 kg marc per day per head, control group (40 females) without marc. Pyrethrum marc may, because of its residual 0.08% pyrethrins have some anthelmintic effect. According to statistical analysis, differences in egg counts between the two supplement fed groups were found to be non significant. Significant differences were found between Group I, Group II and the control Group on the 10th of October (at 5% level), and when the overall means of the egg counts were considered (at 1% level). The copper content of the marc used in the present trial contained only 8 mg and blood copper levels of experimental animals remained within the normal range. There is a definite difference in growth rate among the three groups. The control group weighed virtually the same as did 3.5 months before. Between Group I and II the difference of 23 grams per day was highly significant (9.1%) feeding 0.82kg marc instead of 0.49 kg per head per day during a fixed period results in 18% higher net income if the weight gain is only considered to be “sold”.